A Phase I/II Study of Tazemetostat Combined with Abbreviated Rituximab/Bendamustine Therapy for High Tumor Burden Follicular Lymphoma in Frontline Treatment: A Big Ten Cancer Research Consortium Study - Kenkre, Vaishalee P; Lin, Yong; Epperla, Narendranath; Rajguru, Saurabh A; Chang, Julie E; Pophali, Priyanka A.; Harris, Elyse I; Fletcher, Christopher D; Matasar, Matthew; Eltoukhy, Hussam; Bond, David A.; Sawalha, Yazeed; et al. (Blood, 2024)
Background: Follicular lymphoma (FL) is the most common subtype of indolent B-cell non-Hodgkin lymphoma. Six cycles of bendamustine and rituximab (BR) is standard of care for high tumor burden follicular lymphoma (HTBFL). In the BRIGHT trial (Flinn IW et al, Blood 2014), the CR rate after 6 cycles of BR for FL was only 30%, but later studies have reported CR rates around 60% (Hill BT et al, Br J Haem 2019; Evens AM et al, Clin Canc Res 2020). Treating patients with HTBFL with therapy that is both efficacious and well tolerated is an important goal, given the incurable nature of the disease and need for subsequent therapies. Tazemetostat is an oral S-adenosyl-methionine-competitive small molecule inhibitor of EZH2, manufactured by Ipsen. EZH2 gain of function mutations are seen in about 25-30% of FL. Tazemetostat was approved by the FDA in June 2020 for relapsed/refractory FL. It has activity in both EZH2 mutated and wild-type FL. We designed a phase I/II study via the Big Ten Cancer Research Consortium integrating tazemetostat with frontline BR, which aimed to maintain efficacy but minimize side effects of cytotoxic chemotherapy. Methods: Treatment consists of 3 cycles of tazemetostat plus BR followed by 3 cycles of tazemetostat and rituximab. Subjects had to have low grade FL, untreated (except allowed to have prior local radiation therapy, up to 4 doses of rituximab, and/or steroids for symptom control), meet GELF HTBFL criteria, and stage II-IV disease. EZH2 status is being evaluated as a correlative endpoint, but not required at study entry. The primary endpoint of the phase I portion is to establish the safety and tolerability of tazemetostat in combination with BR. The primary endpoint of the phase II study is the CR rate with 3 cycles of BR plus tazemetostat followed by 3 cycles of rituximab plus tazemetostat, which was predicted to have equal to or better efficacy than 6 cycles of BR. We completed accrual to the phase I portion of the study and results are presented here. Accrual to the phase II portion is ongoing. The phase I portion consisted of a traditional 3+3 design, with 3 tazemetostat dose levels (400mg, 600mg, and 800mg twice daily [BID]). All subjects received tazemetostat BID on days 1-28 in combination with bendamustine 90 mg/m2 IV on days 1 & 2 and rituximab 375 mg/m2 IV on day 1 of a 28-day cycle for up to 3 cycles. Following this, subjects received tazemetostat BID on days 1-28 and rituximab 375 mg/m2 IV on day 1 of a 28-day cycle for 3 cycles. The maximum tolerated dose (MTD) was defined as the dose level at which no more than 1 subject experienced a dose limiting toxicity (DLT) out of 6 patients. For the determination of the MTD, DLTs were evaluated within the first cycle (i.e., within the first 28 days). For non-hematologic toxicities, DLT was defined as any CTCAE v5.0 Grade 3 or greater attributed to study treatment. For hematologic toxicities, DLT was defined as Grade 4 neutropenia, Grade 3-4 thrombocytopenia, or any hematologic toxicity that was grade 5 attributed to study treatment. Results: There were 12 HTBFL subjects enrolled and treated in the phase I portion of this study. Median age was 64.5 years (range 44-72). Ann Arbor Stage was 4 (n = 6), 3 (n=5), and 2 (n=1). All subjects completed the planned 6 total cycles of therapy. Six of 12 subjects were treated at the MTD dose of 800mg BID. There were no DLTs. Further, no clinically significant grade 4-5 adverse events were seen. Clinically significant Grade 3 AEs consisted of: leukopenia (n=2), neutropenia (n=1), anemia (n=1), atrial fibrillation (n=1), bone pain (n=1), infection (n=2), and infusion related reaction (n=1). Response assessment was conducted by PET imaging after cycles 3 and 6. Ten of 12 subjects (83%) had a complete metabolic response (CMR) after 3 cycles; one had partial metabolic response; and one with CT imaging, thus could not be assessed for metabolic remission. At the end of planned treatment (EOT), 9 subjects had a CMR, 3 are awaiting EOT assessment at the time of this abstract submission. Conclusions: The combination of tazemetostat with abbreviated BR therapy for patients with HTBFL was overall well tolerated and no DLT was identified. In addition, the CMR rate in the phase I portion for patients who have had EOT assessment is 100%. The MTD was 800 mg BID and was chosen for the ongoing phase II portion of the study. Kenkre:Ipsen: Research Funding. Epperla:Lilly: Other: Advisory Board; Beigene: Speakers Bureau; Ispen: Other: Advisory Board; Novartis: Consultancy; Genetech: Speakers Bureau. Chang:BeiGene: Consultancy; Abbvie: Consultancy; Genentech: Research Funding; ONO Pharmaceuticals: Consultancy; Celgene/BMS: Research Funding. Pophali:Marker Therapeutics: Research Funding; Fate Therapeutics: Research Funding; SeaGen: Honoraria, Membership on an entity's Board of Directors or advisory committees, Research Funding. Matasar:Pfizer: Honoraria; Genentech: Consultancy, Honoraria, Research Funding; Immunovaccine Technologies: Research Funding; Seattle Genetics: Consultancy, Honoraria, Research Funding; Roche: Consultancy, Honoraria, Research Funding; BMS/Celgene: Honoraria; Johnson & Johnson: Consultancy, Honoraria, Research Funding; AstraZeneca: Honoraria; Pharmacyclics: Consultancy, Honoraria, Research Funding; ADC Therapeutics: Honoraria; Takeda: Honoraria; IMV Therapeutics: Honoraria; Epizyme: Honoraria; Kite: Honoraria; GM Biosciences: Consultancy, Research Funding; Bayer: Consultancy, Honoraria, Research Funding; Genmab: Membership on an entity's Board of Directors or advisory committees; Allogene: Membership on an entity's Board of Directors or advisory committees; Merck: Current equity holder in publicly-traded company; Regeneron Pharmaceuticals, Inc.: Honoraria. Bond:Nurix Therapeutics: Consultancy, Research Funding; ADC Therapeutics: Consultancy; Kite/Gilead: Research Funding; AstraZeneca: Research Funding; BMS: Research Funding; Incyte: Research Funding; Accutar: Research Funding; GenMab: Research Funding; Novartis: Consultancy, Research Funding. Sawalha:AbbVie: Research Funding; Genmab: Honoraria, Research Funding; ADC: Consultancy; Beigene: Research Funding. Christian:Acerta: Research Funding; Astra Zeneca: Honoraria; Ipsen: Honoraria; Genentech: Research Funding; Millenium: Research Funding; Bristol Myers Squibb: Research Funding. Voorhees:Kite: Research Funding; Novartis: Consultancy; Recordati: Consultancy, Research Funding; AbbVie: Membership on an entity's Board of Directors or advisory committees, Research Funding; Genmab: Consultancy, Membership on an entity's Board of Directors or advisory committees, Research Funding; Viracta: Research Funding; Incyte/Morphosys: Research Funding. Evens:Incyte: Consultancy, Honoraria; Daiichi Sankyo: Consultancy, Honoraria; Genentech: Consultancy, Honoraria; Novartis: Consultancy, Honoraria; Pharmacyclics: Consultancy, Honoraria; Pfizer: Consultancy, Honoraria. tazemetostat in frontline treatment of follicular lymphoma